City beautiful - Gerald A. Carlino; Albert Saiz (Institute for the Study of Labor (IZA), 2008)
The city beautiful movement, which in the early 20th Century advocated city beautification as a way to improve the living conditions and civic virtues of the urban dweller, had languished by the Great Depression. Today, new urban economic theory and policymakers are coming to see the provision of consumer leisure amenities as a way to attract population, especially the highly skilled and their employers. However, past studies have only provided indirect evidence of the importance of leisure amenities for urban development. In this paper we propose and validate the number of leisure trips to MSAs as a measure of consumer revealed preferences for local leisure-oriented amenities. Population and employment growth in the 1990s was about 2 percent higher in an MSA with twice as many leisure visits: the third most important predictor of recent population growth in standardized terms. Moreover, this variable does a good job at forecasting out-of-sample growth for the period 2000-2006. Beautiful cities disproportionally attracted highly-educated individuals, and experienced faster housing price appreciation, especially in supply-inelastic markets. Investment by local government in new public recreational areas within an MSA was positively associated with higher subsequent city attractiveness. In contrast to the generally declining trends in the American central city, neighborhoods that were close to central recreational districts have experienced economic growth, albeit at the cost of minority displacement.
urn:nbn:de:101:1-20081126376
Keywords: J11; 330; Internal migration; amenities; urban population growth; Stadtentwicklung; Kommunalplanung; Grünfläche; Erholungsgebiet; Sportanlage; Stadtwachstum; USA